2009
DOI: 10.2146/ajhp080031
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-size distribution and stability of lipid injectable emulsions

Abstract: Multiple lots of a lipid emulsion were found to have acceptable PFAT(5) and mean droplet-size values, regardless of oil content, container size, or storage time and tempearture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…All data are presented as the mean ± standard deviation (SD). The PFAT 5 values are in agreement with the previously reported data by Gallegos et al (2009).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…All data are presented as the mean ± standard deviation (SD). The PFAT 5 values are in agreement with the previously reported data by Gallegos et al (2009).…”
Section: Introductionsupporting
confidence: 92%
“…It was demonstrated that Intralipid since October 2006 complies with the limit (Driscoll, 2009), well in advance of the introduction of the droplet size monograph in the USP in December 2007. The adherence of Intralipid in plastic packaging to the USP limit has previously also been addressed and verified by other authors (Gallegos et al, 2009). …”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Commercially prepared IVFE has a mean particle size (MPS) of about 0.33–0.4 µm in diameter 25 . At this size range, the IVFE particle mimics naturally occurring chylomicrons.…”
Section: Particle Sizementioning
confidence: 99%
“…Droplet size distribution is of great importance because of its fundamental information about many characteristics such as the rheology [27], the stability of emulsion and performance of stabilizers [28]. According to the stocks law, the velocity of phase separation in an emulsion is proportional to the square of its dispersed phase radius.…”
Section: Particle Size Distributionmentioning
confidence: 99%